The Influence of Media and Reputation on Sustainability Reporting Disclosure - Hamidi, Barzan; Zarefar, Arumega; Mayla Khoiriyah; Satriawan, Raja Adri; Ramaiyanti, Sinta; Afifah, Ulfa; Zarefar, Atika (Journal of Financial and Behavioural Accounting, 2024)
This study aims to determine the influence of media visibility, social media, and company's reputation on the disclosure of sustainability reports on technology and health sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2014-2022. This research is a quantitative study that uses secondary data, sourced from annual reports disclosed on IDX and the company's website and corporate social media. The population of this study is technology and health sub-sector companies listed on the IDX in 2014-2022. Data from this study used 15 companies with nine years of observation using purposive sampling techniques so that 135 samples were obtained.  Data analysis techniques used in research are classical assumption test analysis, regression test, and t test using STATA 17 software. The results of this study show that media visibility is influence on sustainability reporting disclosure, social media is not influence sustainability reporting disclosure, and company's reputation is not on sustainability reporting disclosure. - The results in this study cannot be generalized, because the scope of this study is only limited to the technology and health sub-sectors.